A Case of Idiopathic Recurrent Spontaneous Bladder Rupture. (30th August 2021) - Bartholomew, Reid; Ahmeti, Mentor
Abstract : Background . A female patient presented four years following spontaneous bladder rupture with a recurrent spontaneous bladder rupture. Summary . Urinary bladder rupture is a condition usually caused by trauma or surgical instrumentation. Spontaneous bladder rupture is a much more uncommon condition and is associated with intoxication, radiation, stricture, or neurogenic bladder. We describe a case of a 40-year-old woman with a history of three caesarian sections with an idiopathic recurrent spontaneous bladder rupture. Originally, she presented with one day of worsening severe abdominal pain. CT showed possible ischemic bowel. She was taken to the operating room (OR) and found to have a bladder rupture. This was repaired, and she did well postoperatively. Four years later, she presented to the emergency department (ED) with one week of worsening abdominal pain that became severe acutely. Given that she had a similar issue four years prior the patient was suspicious, her bladder was again ruptured. CT cystogram showed contrast extravasation into the peritoneum. The patient was taken urgently to the operating room for an open repair of the bladder rupture. She did well following the procedure. Conclusion . Spontaneous bladder rupture is a surgical emergency and should be in the differential diagnosis of any patient with peritonitis with elevated creatinine and free intraperitoneal fluid. This diagnosis should especially be considered if the patient has a history pelvic radiation, neurogenic bladder, or intoxication. We submit that a history of multiple pelvic surgeries should be included in this list. CT cystogram is the diagnostic test of choice. Operative repair is generally the treatment for this condition.